Vibration Control of Base-Excited Rotors Supported by Active Magnetic Bearing Using a Model-Based Compensation Method - Zhang, Peng; Zhu, Changsheng (IEEE transactions on industrial electronics (1982), 2024)
Active magnetic bearings (AMBs) are a type of mechatronics product widely used in high-speed rotating machinery. Considerable research has been conducted on the vibration rejection of the AMBs-rotor systems at the base standstill. However, little attention has been paid to the case where the rotor operates under base excitations, such as turbines mounted on ships with wave excitation. The increased rotor vibration caused by base excitations is a great challenge to operational safety. To address this issue, a base acceleration feedforward compensation (BAFC) algorithm was proposed in this article. Using the online base excitation data and the dynamic model of the rotor system, the proposed model-based algorithm determines the optimal compensation current in real time. Further, to reject the decreased compensation performance due to inaccurate modeling, a method for correcting the compensation error has been presented. Moreover, the effect of controller parameters on system stability was explored to avoid parametric instability during base excitations. By employing the BAFC algorithm in the experiments, the rotor vibration was reduced considerably under both the harmonic and random base excitations with a maximum vibration reduction of 85%, demonstrating the remarkable effectiveness of the BAFC algorithm.